PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP TINDAKAN WANITA USIA SUBUR DALAM DETEKSI DINI KANKER SERVIKS MELALUI PEMERIKSAAN TEST IV A - Nuraini aini; Marinta Ulina (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2020)
Based on a preliminary survey conducted by researchers in the area of ​Desa Baru, Kecamatan Pancur Batu, Kabupaten Deli Serdang, WUS who had a partner who did an VIA test, in the January-August period as many as 125 people and 11 of them were found positive. The purpose of this study was to determine the effect of internal and external factors on the actions of women of childbearing age in the early detection of cervical cancer through an VIA test. The research method uses analytic survey design with cross sectional approach where primary data is obtained by distributing questionnaires and secondary data is seen from the health center health book profile. Sampling using proportional random sampling. The study was conducted in April with a sample of 100 people from 1019 total populations. Data analysis used chi-square test analysis techniques. The results of the study of 100 respondents 55% aged 18-35 years old, 41% secondary education, 66% working, 59% low income, 63% multiparous mothers, 72% poor knowledge and 53% receive information through the media. Chi-square test results have the influence of internal factors and external factors on the actions of women of childbearing age in the early detection of cervical cancer through an VIA test. For internal factors, a p-value of 0.001 is obtained for age, 0,000 for work, and 0.008 for parity, while for external factors a p-value of 0,000 for knowledge and 0.002 for information sources is obtained. And the most influential is the mother's knowledge factor with a Sig value of 0,000 (OR 15,458). Suggestions for respondents are expected to seek health information about cervical cancer prevention and VIA test so that women of childbearing age get optimal and early health services from local health workers. And health workers, are expected to further enhance their role in providing health information about early detection of cervical cancer through VIA test.